L’écriture du monde (II). - Nicolas Perreaux (Bulletin du Centre d’Études Médiévales d’Auxerre)
The regionalization of medieval writing is still an unclear question. Through various methods borrowed from Text Mining, the article seeks primarily to better define the forms and extent of the geographic variability of the diplomatic vocabulary. Alternating scales (qualitative and qualitative), it shows that the regionalization process vary depending on the frequency of words – from the « endemic » vocabulary to the complex formula, through the « current » vocabulary. With the implemented techniques we can observe the movement of the vocabulary in a scriptorium (Cluny) and then compare all the lexicon of various institutions. Ultimately, the work finds strong regionalization processes of the diplomatic lexicon, from the tenth century in some areas. Conversely, the Merovingian and Carolingian periods do not seem to follow strong lexical regionalization. At European level, the analyzes also show a gradual standardization of the lexicon between 1150 and 1350, which we compare to the formation of Europe itself – because it does not prevent regionalization, promoting instead the reconciliation of a universal Church (Ecclesia) and local churches. This « ecclesiastical paradox » and the written word are then approached in a semantic analysis, through the lemmas aqua and terra. Often close to the writing, the aqua meanings are followed in the CEMA and Patrologia Latina. It is then deduced that the water was a pure and spiritual element that favored, like writing, the transitus – i.e. the passage from carnal to the spiritual ; meanwhile terra oscillated between rejection and hyper-valuation. Following a structural study, the article proposes the hypothesis that the passage of a terra by an ecclesial writing amounted to a baptism, that is to say to a form of spiritualization.